Prediction of Intact N-Glycopeptide Retention Time Windows in Hydrophilic Interaction Liquid Chromatography - Kozlik, Petr; Molnarova, Katarina; Jecmen, Tomas; Krizek, Tomas; Bosakova, Zuzana (Molecules (Basel, Switzerland), 2022)
Analysis of protein glycosylation is challenging due to micro- and macro-heterogeneity of the attached glycans. Hydrophilic interaction liquid chromatography (HILIC) is a mode of choice for separation of intact glycopeptides, which are inadequately resolved by reversed phase chromatography. In this work, we propose an easy-to-use model to predict retention time windows of glycopeptides in HILIC. We constructed this model based on the parameters derived from chromatographic separation of six differently glycosylated peptides obtained from tryptic digests of three plasma proteins: haptoglobin, hemopexin, and sex hormone-binding globulin. We calculated relative retention times of different glycoforms attached to the same peptide to the bi-antennary form and showed that the character of the peptide moiety did not significantly change the relative retention time differences between the glycoforms. To challenge the model, we assessed chromatographic behavior of fetuin glycopeptides experimentally, and their retention times all fell within the calculated retention time windows, which suggests that the retention time window prediction model in HILIC is sufficiently accurate. Relative retention time windows provide complementary information to mass spectrometric data, and we consider them useful for reliable determination of protein glycosylation in a site-specific manner.
Keywords: hydrofobní a hydrofilní interakce; retention time prediction; glycopeptides; chromatografie s reverzní fází; glykopeptidy; Hydrophobic and Hydrophilic Interactions; hemopexin; Chromatography, Reverse-Phase; Glycosylation; glycoproteomics; sex hormone-binding globulin; Chromatography, Liquid; hydrophilic interaction liquid chromatography; glycopeptide separation; Glycopeptides; chromatografie kapalinová; glykosylace; haptoglobin